Enhancing Employee Performance: The Effect of Job Satisfaction, Motivation, Workload, and Work Discipline - Giovany, Rina; Suyana, Hilma (Human Capital and Organizations, 2024)
This study aims to determine the effect of Job Satisfaction, Motivation, Workload and Work Discipline on the Performance of PT. Source of Alfaria Trijaya Tbk in East Pademangan Region, North Jakarta and its review from an Islamic point of view. The population in this study are employees of PT. Sumber Alfaria Trijaya Tbk in East Pademangan Area, North Jakarta. Data was collected by survey method with a questionnaire instrument. The data analysis method used is multiple regression analysis. The results of the study show that (1) Partial Job Satisfaction has a positive and significant influence on employee performance. (2) Partial Motivation does not have a positive and significant influence on employee performance. (3) Partially, Workload does not have a positive and significant influence on employee performance; (4) Partially, Work Discipline has a positive and significant effect on employee performance. (5) Simultaneously, Job Satisfaction, Motivation, Workload and Work Discipline have a positive and significant influence on Employee Performance. The managerial implications of this research indicate that to improve employee performance, companies must focus on increasing job satisfaction, motivation and work discipline, as well as effective workload management.